Pathogenic gene variants in CCDC39, CCDC40, RSPH1, RSPH9, HYDIN, and SPEF2 cause defects of sperm flagella composition and male infertility - Aprea, I.; Wilken, A.; Krallmann, C.; Nöthe-Menchen, T.; Olbrich, H.; Loges, N. T.; Dougherty, G. W.; Bracht, D.; Brenker, C.; Kliesch, S.; Strünker, T.; Tüttelmann, F.; et al. (Frontiers in Genetics, 2023)
Primary Ciliary Dyskinesia (PCD) is a rare genetic disorder affecting the function of motile cilia in several organ systems. In PCD, male infertility is caused by defective sperm flagella composition or deficient motile cilia function in the efferent ducts of the male reproductive system. Different PCD-associated genes encoding axonemal components involved in the regulation of ciliary and flagellar beating are also reported to cause infertility due to multiple morphological abnormalities of the sperm flagella (MMAF). Here, we report ten infertile male individuals with pathogenic variants in CCDC39 (one) and CCDC40 (two) encoding ruler proteins, RSPH1 (two) and RSPH9 (one) encoding radial spoke head proteins, and HYDIN (two) and SPEF2 (two) encoding CP-associated proteins, respectively. We obtained a detailed clinical history and performed PCD diagnostic including immunofluorescence-, transmission electron-, and high-speed video microscopy on sperm flagella and andrological work up including semen analyses. We demonstrate for the first time that pathogenic variants in RSPH1 and RSPH9 cause male infertility due to sperm cell dysmotility and abnormal flagellar RSPH1 and RSPH9 composition. We also provide novel evidence for MMAF in HYDIN- and RSPH1-mutant individuals. We show absence or severe reduction of CCDC39 and SPEF2 in sperm flagella of CCDC39- and CCDC40-mutant individuals and HYDIN- and SPEF2-mutant individuals, respectively. Thereby, we reveal interactions between CCDC39 and CCDC40 as well as HYDIN and SPEF2 in sperm flagella. Our findings demonstrate that immunofluorescence microscopy in sperm cells is a valuable tool to identify flagellar defects related to the axonemal ruler, radial spoke head and the central pair apparatus, thus aiding the diagnosis of male infertility. This is of particular importance to classify the pathogenicity of genetic defects, especially in cases of missense variants of unknown significance, or to interpret HYDIN variants that are confounded by the presence of the almost identical pseudogene HYDIN2.